3 ナンキョク ノ キンルイ ニ カンスル ケンキュウ 1. ケンキュウシ ナンキョク VICTORIA LAND ノ DRY VALLEY チョウサ ホウコク - 杉山, 純多; スギヤマ, ジュンタ; 杉山, 佳子; スギヤマ, ヨシコ; 飯塚, 広; イイヅカ, ヒロシ; SUGIYAMA, Junta; SUGIYAMA, Yoshiko; IIZUKA, Hiroshi (国立極地研究所, 1967)
P(論文) The present authors reviewed the history of research and contributions in Antarctic mycology. Beginning with the first original study by EKELOF (1907, 1908) on the molds from the soil at Snow Hill Island, east coast of the Antarctic Peninsula (material collected during the Swedish Antarctic Expedition of 1901-1903, led by NORDENSKJOLD), a number of reports concerning the fungi in Antarctica have been made in subsequent years. Particularly since the International Geophysical Year, 1957-1958, many studies have been made by mycologists of the fungi in Antarctica, e. g., Phycomycetes (HARDER and PERSIEL, 1962), yeasts (DI MENNA, 1960, 1966a, 1966b SONEDA, 1961), molds (TUBAKI, 1961a, 1961b CORTE and DAGLIO, 1962, 1963 TUBAKI and ASANO, 1965), and mushrooms (SINGER, 1954, 1957 SINGER and CORTE, 1962). Recently, SIEBURTH (1965) presented a comprehensive review on the development of studies in microbiology of Antarctica in general. departmental bulletin paper